Correlation of Intravoxel Incoherent Motion Parameters and Histological Characteristics From Infiltrated Marrow in Patients With Acute Leukemia. Issue 6 (18th November 2019) - Li, Jianting; Zheng, Rong; Niu, Jinliang; Song, Xiaoli; Wu, Wenqi; Fan, Rong; Gong, Tong
Abstract : Background: An accurate and noninvasive method is of great importance to assess angiogenesis and cellularity of bone marrow in acute leukemia (AL). Purpose: To investigate whether the intravoxel incoherent motion (IVIM) parameters correlate with the histological characteristics of infiltrated marrow in AL patients and compare the difference between acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). Study Type: Prospective. Population Model: Forty newly diagnosed patients with AL, including 20 AML and 20 ALL. Field Strength/Sequence: 1.5T/T1 WI and IVIM. Assessment: IVIM‐derived parameters (true diffusion coefficient D, pseudodiffusion coefficient D *, and perfusion fraction, f ) were measured in lumbar marrow. Histopathological analyses were performed from samples of marrow biopsy. Statistical Tests: The correlations between IVIM parameters and histological parameters used the Spearman correlation test. The difference of IVIM parameters and histological parameters between ALL and AML groups used the unpaired t ‐test or Mann–Whitney U ‐test, as appropriate. Results: The f was positively correlated with microvessel density (MVD) in patients with ALL, AML, and AL ( r = 0.740, P = 0.006; r = 0.771, P  < 0.001; and r = 0.750, P  < 0.001, respectively). There were no significant correlations between D and bone marrow cellularity in the three groups ( r = –0.289, P = 0.362; r = 0.281, P = 0.292; and r = 0.058, P = 0.769, respectively). D and f values of ALL were higher than that of AML group ( t = 3.332, P = 0.003 and t = 2.600, P = 0.014, respectively). MVD was higher in ALL than AML ( t = 2.120, P = 0.044), whereas bone marrow cellularity had no significant difference between AML and ALL ( t = –0.682, P = 0.501). Data Conclusion: The f value derived from IVIM in bone marrow was positively correlated with MVD, while f might be able to show a difference of vascularity between ALL and AML. Therefore, the f value can be used as an alternative imaging marker of angiogenesis in marrow of AL patients. Level of Evidence : 1 Technical Efficacy Stage : 3 J. Magn. Reson. Imaging 2020;51:1720–1726.